Evaluation of sorghum stover based complete rations with different roughage to concentrate ratio for efficient microbial biomass production by using In vitro gas production technique - Ramana Reddy, Y.; Nalini, K.N.; Monika, T.; Pavani, M.; Sridhar, K. (Diva Enterprises Private Limited, 2015)
An in vitro study was conducted to evaluate the optimum roughage to concentrate ratio in complete rations using sorghum stover (SS) as a roughage source since it is a main feed resource for urban and peri-urban dairies. Eight complete rations were prepared with roughage (R) to concentrate (C) ratio of 100R:0C to 30R:70C. In vitro gas production (ml) at 24 h incubation, in vitro organic matter digestibility and metabolizable energy, truly digestible organic matter and ammonia nitrogen production were increased linearly (P<0.01) as the proportion of concentrate was increased in the ration. Significantly higher (P<0.01) total volatile fatty acid concentration was observed in 50R:50C, 40R:60C and 30R:70C compared to other rations. Significantly (P<0.01) highest partitioning factor, microbial biomass production and efficiency of microbial biomass production were recorded at 60R:40C ratio followed by 50R:50C. Therefore, the present study suggested that SS can be included in complete rations for ruminants at the level of 60 per cent for economic milk and meat production.